Answer:
Helena gave the answer as (7y²z + 6yz²- 5 - 3yz² + 2) which is equivalent to (7y²z + 3yz² - 3).
Step-by-step explanation:
Misha's group was asked to write an expression equivalent to
7y²z + 3yz² - 3
When Mr. Chen checked their answers, he found only one to be correct.
And she was Helena.
Helena gave the answer as (7y²z + 6yz²- 5 - 3yz² + 2) which is equivalent to (7y²z + 3yz² - 3).
Because, (7y²z + 6yz²- 5 - 3yz² + 2)
= 7y²z + (6yz² - 3yz²) - (5 - 2)
= 7y²z + 3yz² - 3 (Answer)
Answer: 
Step-by-step explanation:
Here w shows the number of weeks and t shows the total amount in w weeks.
Since, the initial amount he paid to her = $ 50
After that he paid $ 5 per week.
Thus, the total extra amount he paid = 5 w
⇒ The total amount he paid to her = 50 + 5 w
⇒ t = 50 + 5 w
Which is the required relation between the total amount paid(t) and the number of weeks (w) Jake will take to pay Luna.
Answer:
8000in³
Step-by-step explanation:
20³=20*20*20=8000